Beginning C 4th Edition - Horton, Ivor (Apress, 2012)
Welcome to Beginning C: From Novice to Professional, Fourth Edition. With this book you can become a competent C programmer. In many ways, C is an ideal language with which to learn programming. C is a very compact language, so there isn’t a lot of syntax to learn before you can write real applications. In spite of its conciseness and ease, it’s also an extremely powerful language that’s still widely used by professionals. The power of C is such that it is used for programming at all levels, from device drivers and operating system components to large-scale applications. C compilers are available for virtually every kind of computer, so when you’ve learned C, you’ll be equipped to program in just about any context. Finally, once you know C, you have an excellent base from which you can build an understanding of the object-oriented C++. My objective in this book is to minimize what I think are the three main hurdles the aspiring programmer must face: coming to grips with the jargon that pervades every programming language, understanding how to use the language elements (as opposed to merely knowing what they are), and appreciating how the language is applied in a practical context.